(untitled) (Academia Science Repository, 2023)
In school education, chemistry is a subject, the study of which provides the necessary didactic opportunities and means of forming information and communication competence. In recent years, scientists, both theorists and practitioners, have been actively developing the idea of using information technologies to form the professional competencies of future chemistry teachers. At the same time, it is noted that the formation of information and communication competence of a future chemistry teacher at a university based on the methodology of teaching chemistry should be carried out consistently and continuously.